Improving English Reading Comprehension via Murdoch Integrated Approach on Students of Grade 5 in Thailand - Weerawong, Prissana; Chano, Jiraporn; Wu, Chicheng (Journal of Language Learning and Assessment, 2025)
Purpose This study aimed to test the effect of the Murdoch Integrated Approach (MIA) on English reading comprehension and analytical reading skills among Thai Grade 5 students. Methodology A one-group pretest-posttest design was employed with 37 Grade 5 students as participants. The intervention consisted of eight 16-hour MIA learning sessions conducted over one semester. Two 30-item multiple-choice tests—one for reading comprehension and one for analytical reading—were administered before and after the intervention. The tests were validated by experts, with Item-Objective Congruence (IOC) values between 0.60 and 1.00. Discrimination indices and reliability coefficients were also reported for both tests. Results/Findings Dependent t-test results showed significant improvements in both reading comprehension and analytical reading scores. Reading comprehension scores increased from 15.08 to 20.78 (t(36) = 9.5, p < .000), and analytical reading scores improved from 14.57 to 18.11 (t(36) = 8.77, p < .000). Implication These findings suggest that the Murdoch Integrated Approach has potential to enhance students' reading skills. However, the absence of a control group means findings should be interpreted with caution. Future research using a true experimental design is recommended to provide stronger evidence of MIA's effectiveness